THE BUILDING PLAN APPROVAL PROCESS FOR RESIDENTIAL DEVELOPMENT IN ONE STOP CENTRE. CASE STUDY: SUBANG JAYA MUNICIPAL COUNCIL, SELANGOR - Marzukhi, Marlyana Azyyati; Hoon Leh, Oliver Ling; Khalid, Nurul Shakila; Jaafar, Azfarnizam (Journal of Surveying, Construction and Property, 2020)
The building plan approval involved with regulations, laws and guidelines to ensure systematic and orderly development. The growth in construction activities in Malaysia since the 1980’s has given rise to the need for more statutory controls in obtaining permissions from the relevant authorities to initiate and to construct a facility and upon its completion to occupy and use the completed facility. The understanding of building plan process is important to understand whether the development follows the building regulations. Thus, the construction failures can be limited. Nevertheless, little is known about the effectiveness of building plan process in the local authority though the enhancement of mechanism delivery system of the process known as One Stop Centre (OSC) has been established. The study was conducted to investigate the effectiveness of building plan approval process in Subang Jaya Municipal Council (MPSJ). Forty-seven (47) questionnaires survey has been distributed to respondents from the MPSJ's internal technical departments. Most of the respondents felt that the ineffectiveness of the building plan approval process was due to the incomplete documents submitted to the OSC, lack of knowledge among the Principal Submitting Person (PSP) and the incapability of staffs in handling development applications. The findings present a synthesis of results for town planners, architects, developers and government agencies to have a better understanding of how the effective and efficient building plan process can rationalize the success of property development sector in Malaysia.